An introduction to positive economics - Lipsey, Richard G. (London : Weidenfeld and Nicolson, 1979)
There are three major themes of this text book: first, an attempt to explain what economic theory is about and how one can go about criticizing it effectively and hence improving it; second, an attempt to elaborate, in so far as is possible within the confines of an introduction to economic theory, the relation between theory and real-world observations; and third, a consideration of the relation between economic theory and economic policy.
Includes bibliographical references and index.
rpm 11/07/2017
Loans
Keywords: Economics